Dying in the wool - Brody, Frances (Brody, Frances. Kate Shackleton mystery., 2012)
Bridgestead is a peaceful spot: a babbling brook, rolling hills and a working mill at its heart. Pretty and remote, nothing exceptional happens<U+2026>Until the day that Master of the Mill Joshua Braithwaite goes missing in dramatic circumstances, never to be heard of again. Now Joshua's daughter is getting married and wants one last attempt at finding her father. Has he run off with his mistress, or was he murdered for his mounting coffers? Kate Shackleton has always loved solving puzzles. So who better to get to the bottom of Joshua's mysterious disappearance? But as Kate taps into the lives of the Bridgestead dwellers, she opens cracks that some would kill to keep closed<U+2026>